Becoming past : history in contemporary art - Blocker, Jane (University of Minnesota Press, 2016)
Is there such a thing as contemporary art history? The contemporary, after all - as much as we may want to consider it otherwise - is being made history as it happens. By what means do we examine this moving target? These questions lie at the centre of Jane Blocker's 'Becoming Past'. The important point is not whether there is, or should be, contemporary art history, Blocker argues, but how.